Faslün Fî Usûli'l-İmân Adlı Risale ve Maturidi'ye Aidiyeti - Ak, Ahmet (Dinî araştırmalar, 2006)
In this article, a treatise "entitled "fasl fi usul al-iman" that shows some similarities to to the Maturidite views will be dealt with as to whether it belongs to al-Maturidi or not. Therefore, the views put forth in the treatise have been compared with that of Kitab al-Tawhid and Ta’wilat al-Qur’ân. As a result, it hasa been concluded that the terms used in the treatise such as al-irâda al-juz’iyya, al-irâda al-kulliyya and al-ba‘th ba‘d al-mawt have not been used by al-Maturidi in his works. Thus, it has been argued that the treatise in question was written by a Maturidite school long after the date of Maturidi. Besides, it has been emphasized that this treatise sets an example for the fact that the Asharite views had found their places in the Maturidite sources